Cybercrime vandalising the information society - Furnell, Steven 1970- (Addison-Wesley, 2002)
This overview of computer-based crime and abuse covers a wide range of crimes and abuses, including those involving hackers and computer viruses. Detailed technical knowledge is not needed and there are examples of incidents that have already occurred.
Keywords: Computercriminaliteit; Computervirussen; Culturele aspecten; Juridische aspecten; Kultur; Computer crimes; Internetkriminalität